Hukum Nafkah Terhadap Keluarga pada Gerakan Transnasional Keagamaan - Muhamad Bisri Mustofa, M.Kom.I (International Journal of Publication Unit (IUJP) Agus Salim Metro, 2019)
Abstract Since the emergence of the Transnational Da'wah Movement such as the Tablighi Jama'at, it has created contradictions about the Law of Providing both birth and mentality to the family left in the Khuruj fii sabilillah program (Exiting the Way of Allah) to preach the ummah from house to house, mosque to mosque, inviting listen to Muslims (religious lectures) and invite to pray in congregation in the mosque. From the development of Jama'ah Tabligh's missionary movement in Indonesia, this movement has experienced quite rapid development. Not only is the movement that has a Jama'at quite rapidly, it is marked by the presence of da'wah markers (da'wah centers) in each Province and District of the City. But in the development of the da'wah movement there are several things that become contradictions in the family, in this case the provision of income to children and wives who are left behind when their household heads implement Khuruj fi sabilillah for 3 days, 40 days and 4 months. Therefore, this paper takes the theme of the Law of Livelihood Against Families in the Tabligh Jama Da'wah Movement in a comprehensive manner. Keywords: Family Livelihood, Religious Transnational Movement.